2007
DOI: 10.1007/s11274-006-9325-z
|View full text |Cite
|
Sign up to set email alerts
|

Competition for nodule formation between introduced strains of Mesorhizobium ciceri and the native populations of rhizobia nodulating chickpea (Cicer arietinum) in Tunisia

Abstract: Chickpea is the most cultivated grain legume in the world and it shares the first rank with faba bean in Tunisia. However, the yield remains low, mainly due to the limited availability of N and P, and to the severe bioclimatic conditions. No inoculation trials had been conducted on chickpea in the Tunisian soils. This paper reports the yield response to inoculation by two different strains of Mesorhizobium ciceri, an exogenous type strain (UPMCa7 T ) and a selected local strain (CMG6). Field experiments were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 35 publications
(28 reference statements)
7
34
0
Order By: Relevance
“…Inoculation of the EEL 7802 strain resulted in higher N fixation in the aerial part than in the non-inoculated plants and plants without N fertilization. It was found that the number and mass of nodules of the inoculated pea plants had no correlation with pea grain production, which is in accordance with the observation that the efficiency of N fixation and the competitive capacity of a strain are not necessarily correlated (Romdhane, 2007).…”
Section: Resultssupporting
confidence: 81%
“…Inoculation of the EEL 7802 strain resulted in higher N fixation in the aerial part than in the non-inoculated plants and plants without N fertilization. It was found that the number and mass of nodules of the inoculated pea plants had no correlation with pea grain production, which is in accordance with the observation that the efficiency of N fixation and the competitive capacity of a strain are not necessarily correlated (Romdhane, 2007).…”
Section: Resultssupporting
confidence: 81%
“…In this study, results were obtained using a strain that showed limited symbiotic potentialities (SMCP) that was maintained in our study because in Tunisian soils most of the rhizobia nodulating chickpea belong to the Sinorhizobium genus Ben Rhomdhane et al 2007b). However, to avoid that our conclusions about strain effect might be dependent on the behaviour of one strain only, we analysed the variance without the SMCP strain.…”
Section: Resultsmentioning
confidence: 99%
“…Sinorhizobium meliloti (SMCP) strain from LILM (Laboratoire Interactions Légumineuses Microorganismes, Centre de Biotechnologie de Borj Cedria, Tunisia) collection. This S. meliloti strain was used, since previous works Ben Rhomdhane et al 2007b) showed that in Tunisia, the mainstream of the chickpea nodule isolates were assigned to the Sinorhizobium genus.…”
Section: Biological Materialsmentioning
confidence: 99%
“…To increase the chances of getting efficient strains, the structure and the symbiotic capabilities of indigenous rhizobium populations and their competitiveness should be assessed [83][84][85][86]. This lies in the fact that local strains can be more efficient than exogenous strains that were previously proven to be highly efficient on other legume crops [84,87].…”
Section: Improvement Of Kersting's Groundnut Productivity: Potentialmentioning
confidence: 99%